Postprandial Levels of Branch Chained and Aromatic Amino Acids Associate with Fasting Glycaemia. (5th May 2016) - Ottosson, Filip; Ericson, Ulrika; Almgren, Peter; Nilsson, Jeanette; Magnusson, Martin; Fernandez, Céline; Melander, Olle
Abstract : High fasting plasma concentrations of isoleucine, phenylalanine, and tyrosine have been associated with increased risk of hyperglycaemia and incidence of type 2 diabetes. Whether these associations are diet or metabolism driven is unknown. We examined how the dietary protein source affects the postprandial circulating profile of these three diabetes associated amino acids (DMAAs) and tested whether the postprandial DMAA profiles are associated with fasting glycaemia. We used a crossover design with twenty-one healthy individuals and four different isocaloric test meals, containing proteins from different dietary sources (dairy, fish, meat, and plants). Analysis of the postprandial DMAAs concentrations was performed using targeted mass spectrometry. A DMAA score was defined as the sum of all the three amino acid concentrations. The postprandial area under the curve (AUC) of all the three amino acids and the DMAA score was significantly greater after intake of the meal with dairy protein compared to intake of the three other meals. The postprandial AUC for the DMAA score and all the three amino acids strongly associated with fasting glucose level and insulin resistance. This indicates the importance of the postprandial kinetics and metabolism of DMAAs in understanding the overall association between DMAAs and glycaemia.